Oral Formulation of Posaconazole in Nanosuspension: Development and Optimization by Design of Experiments Approach - Gautham, T. V. (Asian Journal of Pharmaceutics (AJP), 2023)
Introduction: FR and D scientists continuously try to increase the in vivo performance of low soluble and poor bioavailable drugs using various formulation techniques. Nanosuspensions are relatively simple to develop and fall within the novel drug delivery approaches. Materials and Methods: The polymers such as soya lecithin, Tween 80, poloxamer, and polyethylene glycol were used for the preparation. Central composite design was used to optimize the posaconazole nanosuspension and formulation was characterized for various parameters, that is, particle size, morphology and physicochemical parameters were evaluated for in vitro and in vivo performance. Results: Optimized nanosuspension contained an average particle size of 219 ± 0.25 nm and zeta potential was −19.3 ± 6.73 mV. The optimized nanosuspension displayed a significant increase in dissolution profile, by more than 4 folds on average as compared to the drug within 60 min. The results of the pharmacokinetic (PK) study showed the optimized nanosuspension releases the drug with maximum bioavailability as compared to marketed formulation. The formulation found stable up to 6 months. Conclusion: The development of nanosuspension resulted in superior performance in PK effects over the marketed formulation.